(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2026)
Diabetes mellitus and hypertension constitute major non-communicable diseases in Bangladesh, contributing substantially to morbidity, mortality, and economic burden, with limited evidence on medication costs and lifestyle modifications. A multi-stakeholder cross-sectional study was surveyed on 456 participants in Bangladesh, with data collected from Dhaka Medical College Hospital, selected Dhaka city pharmacy areas, professional workplaces, and online platforms using structured questionnaires. Among patients, the majority were aged 40–60 years (57.36%), female (52.83%) and from urban areas (84.53%). Hypertension was alone the most prevalent condition (30.94%), followed by diabetes (29.43%) and comorbid diabetes with hypertension (23.02%). Our study revealed that monthly medication expenses mostly ranged from BDT 1,000 to 5,000, as stated by 50.94% of patients, whilst 13.21% had costs above BDT 5,000. Chi-square analysis demonstrated significant correlations between monthly medication expenses incurred and affordability status (χ²=11.57, p=0.040), disease condition (χ²=48.63, p<0.001), and monthly income (χ²=68.67, p<0.001). Statistical analysis also demonstrated that lifestyle modifications were not significantly associated with the financial cost burden of the patients. Metformin hydrochloride and amlodipine were found to be the most commonly prescribed antidiabetic and antihypertensive drugs respectively. Overall, 87.55% of patients could afford their medications. However, 12.45% patients reported financial hardship. While lifestyle change is commonly viewed as a means to lower costs, healthcare finance, rational prescription, and control of medication prices are crucial for alleviating the economic burden of chronic illness management. Dhaka Univ. J. Pharm. Sci. 25(1): 39-53, 2026 (June)